Cenozoic development of southwestern Malay Basin: new insights from subsidence analysis and thermal history - Hassaan, M. (Springer Verlag, 2017)
Subsidence and thermal history analysis are carried out in order to investigate the Cenozoic basin development of the southwestern (Tenggol Arch and basinal side) part of the Malay basin. Structurally, the southwestern part consists of normal faults and horst and graben geometry. Tectonic subsidence curves show that the basinal side is more active than the Tenggol Arch due to movement along normal faults. Cenozoic development initiated with the deposition of sedimentary Units M & L (Oligocene) and the activation of the Tenggol fault on the basinal side. Several periods of accelerated and slow subsidence are observed during the Oligocene to Middle Miocene that could be associated with changes in regional stresses caused by pulsating plate movement. The Malay Basin experienced inversion throughout the Middle to Late Miocene related to mantle induced slab avalanche effect, causing relatively higher tectonic subsidence rates on the Tenggol Arch compared to the basinal side, suggesting that the Tenggol Arch is less affected by inversion than the basinal side. After a period (Late Miocene) of non-deposition, the basin was reactivated (Pliocene to recent) due to thermal relaxation with thick sedimentation. Paleo heat flows estimated utilizing a novel technique introduced in this study and present day heat flow calibrated using BHT data further supports our results, in that increase in heat flow is related to rapid tectonic subsidence. An anomalously high heat pulse affected the basin during inversion and could be the cause of meta-sediment formation whereas present heat flows, although high compared to average basins, shows decreasing trend from the inversion period. © 2017, Saudi Society for Geosciences.